Ocular Risk Factors for Exudative AMD: A Novel Semiautomated Grading System. (29th July 2013) - Marques, João Pedro; Costa, Miguel; Melo, Pedro; Oliveira, Carlos Manta; Pires, Isabel; Cachulo, Maria Luz; Figueira, João; Silva, Rufino
Abstract : Purpose . To evaluate the contribution of the ocular risk factors in the conversion of the fellow eye of patients with unilateral exudative AMD, using a novel semiautomated grading system. Materials and Methods . Single-center, retrospective study including 89 consecutive patients with unilateral exudative AMD and ≥3 years of followup. Baseline color fundus photographs were graded using an innovative grading software, RetmarkerAMD (Critical Health SA). Results . The follow-up period was 60.9 ± 31.3 months. The occurrence of CNV was confirmed in 42 eyes (47.2%). The cumulative incidence of CNV was 23.6% at 2 years, 33.7% at 3 years, 39.3% at 5 years, and 47.2% at 10 years, with a mean annual incidence of 12.0% (95% CI = 0.088–0.162). The absolute number of drusen in the central 1000 and 3000  μ m (P < 0.05 ) and the absolute number of drusen ≥125 µm in the central 3000 and 6000 µm (P < 0.05 ) proved to be significant risk factors for CNV. Conclusion . The use of quantitative variables in the determination of the OR of developing CNV allowed the establishment of significant risk factors for neovascularization. The long follow-up period and the innovative methodology reinforce the value of our results. This trial is registered with ClinicalTrials.gov NCT00801541 .